2023
DOI: 10.3390/agronomy13112688
|View full text |Cite
|
Sign up to set email alerts
|

Combining Data Assimilation with Machine Learning to Predict the Regional Daily Leaf Area Index of Summer Maize (Zea mays L.)

Yongqiang Wang,
Hui Zhou,
Xiaoyi Ma
et al.

Abstract: The prediction of the daily crop leaf area index (LAI) plays a crucial role in forecasting crop growth trends and guiding field management decisions in the realm of scientific research. However, research on the daily prediction of LAI is scarce, and the challenges associated with acquiring sufficient training data pose limitations to the application of machine learning in this context. This study aimed to synergize the strengths of data assimilation and machine learning algorithms to forecast the daily LAI of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In this study, the phenotypic characteristics of 192 maize accessions were assessed in field conditions as per the Specification and Data Standard for Maize Accessions Description [63]. At maturity, key traits for these accessions were evaluated, including plant height (cm) [64], ear height (cm) [65], ear height to plant height ratio (%) [65], spike leaf length (cm) [66], spike leaf width (cm) [66], leaf length of upper ear (cm) [67], leaf width of upper ear (cm) [67], leaf number [68], effective spike [69], tassel branch number [70], stalk diameter (mm) [71], stem-leaf angle [72], thousand kernel weight (g) [73] and chlorophyll content [74]. A total of 14 traits were characterised.…”
Section: Project Measurementmentioning
confidence: 99%
“…In this study, the phenotypic characteristics of 192 maize accessions were assessed in field conditions as per the Specification and Data Standard for Maize Accessions Description [63]. At maturity, key traits for these accessions were evaluated, including plant height (cm) [64], ear height (cm) [65], ear height to plant height ratio (%) [65], spike leaf length (cm) [66], spike leaf width (cm) [66], leaf length of upper ear (cm) [67], leaf width of upper ear (cm) [67], leaf number [68], effective spike [69], tassel branch number [70], stalk diameter (mm) [71], stem-leaf angle [72], thousand kernel weight (g) [73] and chlorophyll content [74]. A total of 14 traits were characterised.…”
Section: Project Measurementmentioning
confidence: 99%
“…It can also be used to indicate crop biomass, in addition to having correlations with canopy microclimate and evapotranspiration characteristics [3]. In addition, monitoring LAI is essential for predicting crop development and determining crop management throughout the growing season [4]. Han et al [5] observed that an increase in maize plant density leads to an increase in LAI and, consequently, greater light interception.…”
Section: Introductionmentioning
confidence: 99%